2019
DOI: 10.1016/j.foodres.2019.108589
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the bioactive potential of Roselle (Hibiscus sabdariffa L.) calyx and its by-product: Phenolic characterization by UPLC-QTOF MS and their anti-obesity effect in vivo

Abstract: Quantifications and in vivo assays, the data analysis and wrote the draft.Iza F. Peréz-Ramírez: Realized the identification of polyphenolic compounds and organic acids in roselle calyx and by-product by UPLC-QTOF-MS E

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 49 publications
3
39
0
Order By: Relevance
“…Recently, [32] assessed HS calyx and its by-products for bioactive compounds and detected phenolic compounds (14.24 ± 0.77 GAE mg/g), flavonoids (10.37 ± 0.67 CE mg/g), and anthocyanins (5.76 ± 0.43 mg C3 G/g); however, the concentration in the calyx by-product were lower (p < 0.05) by 52.0%, 45.7%, and 57.1%, respectively. Further analysis with ultra-performance liquid chromatograph (UPLC) coupled to a quadrupole time-of-flight (QTOF) mass spectrometer (MSE) identified 34 extractable polyphenols, 3 non-extractable polyphenols, and 2 organic acids in calyx and its by-product.…”
Section: Phytochemical Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, [32] assessed HS calyx and its by-products for bioactive compounds and detected phenolic compounds (14.24 ± 0.77 GAE mg/g), flavonoids (10.37 ± 0.67 CE mg/g), and anthocyanins (5.76 ± 0.43 mg C3 G/g); however, the concentration in the calyx by-product were lower (p < 0.05) by 52.0%, 45.7%, and 57.1%, respectively. Further analysis with ultra-performance liquid chromatograph (UPLC) coupled to a quadrupole time-of-flight (QTOF) mass spectrometer (MSE) identified 34 extractable polyphenols, 3 non-extractable polyphenols, and 2 organic acids in calyx and its by-product.…”
Section: Phytochemical Compositionmentioning
confidence: 99%
“…The calyces are reported to contain potent bioactive ingredients, such as organic acids (citric, malic acids, etc. ), anthocyanins, polysaccharides, and flavonoids [19,[30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Air drying is a comparably cheap and accessible dehydration method. The operation can be run at ambient conditions [53] and high temperatures [16,54,55] by using dried air [56] or even by the natural heating of the sun [14]. Based on research performed by Esparza-Martínez et al, the drying temperature can significantly influence the extraction of non-extractable phenols in mandarin juice waste.…”
Section: By-products Pre-treatmentsmentioning
confidence: 99%
“…Amaya‐Cruz et al. (2019) reported that the administration of Roselle calyx reduced insulin resistance and hepatic steatosis compared with rats fed an HFF diet. Other plant‐derived product employed is cinnamon ( Cinnamomum zeylanicum), and it has been widely used as a food and beverage spreader.…”
Section: Introductionmentioning
confidence: 99%